A Zapotec Facing the Challenge: Globalization and the Demystification of Indigenism in Pancho Culebro and the Naguales of Tierra Azul by Mario Molina Cruz (Revista de Crítica Literaria Latinoamericana, 2014)
The recent decades have witnessed the emergence of a new generation of indigenous writers, one of the most important cultural phenomena in Latin America. The mission of these authors is the recuperation of their native traditions as an alternative system of ethics for our civilization: a decisive challenge to the modern paradigm of economic expansion. The aim of this essay is to explore the contribution of Mario Molina Cruz, one of the most outstanding contemporary writers in the native languages of Mexico (Nezahualcóyotl Prize 2006), to the current debate on the benefits and threats of globalization. The focus is on his bilingual novel, written in Zapotee and Spanish, Xtille zikw belé, Ihén bene nhálhje ke Yu' Bza'o/ Pancho Culebro y los nahuales de Tierra Azul (2006), which illuminates how the author dialogues with the myth of progress upholding the neoliberal capitalist order and indigenist myths that idealize native communities.
Keywords: New Latin American Film; globalization; indigenous literature; spirituality